2020
DOI: 10.1038/s41598-020-76489-1
|View full text |Cite
|
Sign up to set email alerts
|

A model of visual limitation in patients with keratoconus

Abstract: This paper aims to calculate a relevance model of visual limitation (V.L.) in keratoconus patients based on refractive and topographic parameters. A cross-sectional study was carried out in Torrecárdenas Hospital, Almería, Spain, between February 2018 and July 2019. It included 250 keratoconus patients. Two groups were created according to a grading system of V.L. based on RETICS (Red Temática de Investigación Cooperativa en Salud) classification: keratoconus patients with no V.L. (best spectacle-corrected vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Elevated corneal steepness is a hallmark feature of KC. Thus, a protection potential of the AA genotype in KC cannot be excluded [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated corneal steepness is a hallmark feature of KC. Thus, a protection potential of the AA genotype in KC cannot be excluded [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include an increase in maximum corneal curvature by 1 D over a year [ 16 ], increase in astigmatism by 1–3 DC over 6 months, and reduction in central corneal thickness by 5% over 6 months [ 17 ]. Previous studies have demonstrated variable correlation of best-corrected visual acuity with these parameters, with contrast sensitivity again showing a better correlation [ 18 , 19 ]. However, monitoring clinical progression requires specialist imaging equipment, and therefore regular visits to an eye care professional are required.…”
Section: Introductionmentioning
confidence: 99%